A dinâmica das estruturas da agricultura familiar na regi\~ao Centro-Oeste: Uma análise regional por meio de indicadores de localizaç\~ao e especializaç\~ao - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this work, following the guidelines outlined in Pires (2023b and 2023c), is to understand how the agricultural structures of family farming in the Midwest were characterized, in their multi-scale forms, regarding their aspects of location and specialization? To this end, it appears that the agricultural structure of family farming in the Central-West region is reproducing, with due proportions, the more general movement of Central-Western agriculture, which is the regressive specialization in crops conditioned by agricultural commodities such as soybeans and corn, which together accounted for just over 75% of the Valor Bruto da Produç\~ao Agrícola (VBPA) of family farming in 2017. This point becomes extremely important for the debate on food and nutritional security because family farming has a unique role in the process of economic development of a nation, since its function is to produce food aimed at supplying the domestic market and, with this, reducing the risks of food shortages, since everyone has regular and permanent access to food sources and, with this, reduce the danger of hunger and famine. In turn, family farming in the Central-West region, by becoming a major producer of agricultural commodities, soybeans and corn, shifts an important portion of its agricultural production to meet demands coming, in particular, from the economic bloc of China, Hong Kong and Macau, since its agricultural space, with these commodities, is penetrated in a dispersed way and, with this, reaching many municipalities producing soybeans and corn. On the other hand, crops aimed at serving the domestic market are concentrated in a few municipalities, therefore reducing their importance in the family agricultural context of the Central-West region. In this way, the movement of transformation of the agricultural structure of family farming in the Center-West is following the same paths of Ricardian Comparative Advantages experienced for agriculture in general, however, with a specificity, that is, in a scenario of reduced participation of family farming in value of regional production.
Keywords: R11; 330; agricultural structure; family farming; Midwest